2018
DOI: 10.1159/000490616
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Loss during Neoadjuvant Chemotherapy Is an Independent Risk Factor for Postoperative Infectious Complications in Patients with Advanced Esophageal Cancer

Abstract: Objective: Neoadjuvant therapy followed by surgery has been the standard treatment for advanced esophageal cancer. Severe toxicities may influence body composition, including skeletal muscle mass, and increase postoperative complications. The purpose of this study was to evaluate the influence of sarcopenia, changes in body composition, and adverse events during neoadjuvant chemotherapy (NACT) on postoperative complications in esophageal cancer patients. Methods: A total of 83 patients with esophageal cancer u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Recent studies reported that skeletal muscle loss is closely correlated with febrile neutropenia and grade neutropenia (38). One of the reasons is that systemic inflammation due to febrile neutropenia (12). The reduction in skeletal muscle mass is caused by an imbalance in protein metabolism, which is characterized by a significantly smaller muscle fiber crosssectional area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that skeletal muscle loss is closely correlated with febrile neutropenia and grade neutropenia (38). One of the reasons is that systemic inflammation due to febrile neutropenia (12). The reduction in skeletal muscle mass is caused by an imbalance in protein metabolism, which is characterized by a significantly smaller muscle fiber crosssectional area.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of adjuvant chemotherapy can improve OS and the disease-free survival (DFS) (7,8). However, skeletal muscle mass and strength may furtherly be reduced during NAT (9), because of chemotherapy-related toxicities (10), disease progression (11) and adverse postoperative complications (12). Until now, whether sarcopenia would influence the survival rate of EC patients remains controversial (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…28 Skeletal muscle wasting remains to be one of the critical issues in cancer patients, leading to poor survival outcomes, treatment response, and multiple medical issues. 1,[5][6][7][8][9][10][11][12][13] Furthermore, several tumour-related and treatment-related factors can aggravate skeletal muscle degeneration. The tumour itself releases molecules and pro-inflammatory cytokines that can impair the protein synthesis and muscle regeneration mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Skeletal muscle loss and cancer cachexia are also known to be relevant to several medical issues such as prolonged hospitalization, disability, postoperative infections, and other treatment-related toxicities. [11][12][13] Our previous study investigated the relationship between the amount of skeletal muscle loss and the survival outcomes of patients with oesophageal cancer, who received neoadjuvant chemoradiotherapy (NACRT) followed by surgery. 14 We calculated skeletal muscle index (SMI) through computed tomography (CT)-based analysis, one of the most common methods for skeletal muscle mass evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation